2019
DOI: 10.1111/famp.12455
|View full text |Cite
|
Sign up to set email alerts
|

Can Cognitive‐Behavioral Therapy Be Optimized With Parent Psychoeducation? A Randomized Effectiveness Trial of Adolescents With Major Depression in Puerto Rico

Abstract: This is a longitudinal randomized control trial on the impact of adding a parent psychoeducation intervention (TEPSI) as part of cognitive‐behavioral therapy (CBT) for adolescents with Major Depressive Disorder (MDD) in a Puerto Rican sample. We tested the efficacy of adding 8 group sessions of TEPSI to 12 sessions of individual CBT on reducing depressive symptoms, MDD diagnosis, and improving family functioning. Participants (n = 121) were randomized to individual CBT with or without TEPSI. No main group effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 68 publications
1
47
0
Order By: Relevance
“…Considering and integrating the sociocultural values that are commonly held within Puerto Rican communities can impact the effectiveness of interventions. Previous research has detailed how to integrate values such as familism and personalism into interventions, for example by providing parent psychoeducation, allowing the family greater participation in defining their problems and needs, jointly developing interventions goals that are congruent with the family’s expectations, addressing family emotional involvement, and when appropriate, engaging extended family members that play important roles within the unit (Bernal et al, 2019; Parra Cardona et al, 2012; Zayas & Palleja, 1988). The generalizability of our findings to other Latinx and other racial/ethnic minority communities within the US requires future examination.…”
Section: Discussionmentioning
confidence: 99%
“…Considering and integrating the sociocultural values that are commonly held within Puerto Rican communities can impact the effectiveness of interventions. Previous research has detailed how to integrate values such as familism and personalism into interventions, for example by providing parent psychoeducation, allowing the family greater participation in defining their problems and needs, jointly developing interventions goals that are congruent with the family’s expectations, addressing family emotional involvement, and when appropriate, engaging extended family members that play important roles within the unit (Bernal et al, 2019; Parra Cardona et al, 2012; Zayas & Palleja, 1988). The generalizability of our findings to other Latinx and other racial/ethnic minority communities within the US requires future examination.…”
Section: Discussionmentioning
confidence: 99%
“…The general proportion of caregiver/family involvement was the highest in these eight studies; however, no individual session was extended to children/adolescents or caregivers. In contrast, we found seven studies that explicitly integrated the caregivers in all sessions, but no siblings or other family members (Asarnow et al, 2002; Bernal et al, 2019; Clarke et al, 1999, 2002; Fristad et al, 2002; Lewinsohn et al, 1990; Luby et al, 2018). When examining these data, it appears that the earlier studies in particular tended to explicitly include only the caregivers, implementing caregiver involvement mostly through parallel group programmes.…”
Section: Resultsmentioning
confidence: 85%
“…In the investigations that studied family interventions (no individual sessions), we noted that in each intervention described, the focus was on a change in interaction (Brent et al, 1997; Dietz et al, 2015; Tompson et al, 2017), attachment (Diamond et al, 2002, 2010; Israel & Diamond, 2013; Waraan et al, 2020), or relationship (Luby et al, 2018). Apart from those studies, we observed a focus on caregiver/family psychoeducation on depression via several interventions, particularly evident in those that conducted separate caregiver sessions (Bernal et al, 2019; Clarke et al, 1999, 2002; Fristad et al, 2002; Lewinsohn et al, 1990). Asarnow et al (2002) revealed the most limited caregiver involvement, but they only addressed depression and family‐related themes explicitly in their sessions with children and adolescents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach was intended to be used alongside calculation of the RCI, which takes into account the risk of measurement error in interpreting a change score. In our review, three trials analysed Jacobson and Truax' concept of "clinical significance" (Clarke et al, 2005;Hayes et al, 2011;Rossello & Bernal, 1999), and four calculated the RCI (Bernal et al,;Diamond et al, 2019;Hayes et al, 2011;Israel & Diamond 2013). Although a handful of trials had some convincing justification for their dichotomization, the majority of definitions of dichotomized outcomes did not report any empirical support for their use.…”
Section: Rationale For Metric Strategies and Methods Of Aggregation Used In Dichotomized Outcomesmentioning
confidence: 99%